A feasibility study on space-based solar power for lunar economy - Ramala, Sumanth Kumar Reddy; Garzaniti, Nicola (American Institute of Aeronautics and Astronautics (AIAA), 2025)
Energy solutions are essential for the exploration and establishment of long-term lunar activities. Re-energized rush for lunar adventures in the near term and future, alongside investigation of lunar bases in the upcoming years. Most of the current mission functions for a relatively short lifetime of research activities, and they include continual testing with landers to test the survivability of stringent temperatures on the lunar with varying levels of autonomy, resulting in new insights, and requirements for future settlements over the Moon ultimately paving step towards Mars colonization. Current suggested or planned power sources have Batteries, Fission Surface Power, and Vertical Solar Array Technology (VSAT) may encounter hurdles in terms of efficacy, scalability, significant system failures over time due to harsh space weather and lunar environment, and specially during the long prolonged lunar nights. To overcome the obstacles posed in the lunar environment, an innovative technique called Space-Based Solar Power (SBSP) is a prospective option to support lunar explorations, and infrastructure. A systems engineering breakdown approach is employed to explore the feasibility study of the proposed technology. That led to the breakdown of each step as a requirement to address the needs. The whole architecture is partitioned into data set formation of current, future, and past missions, where this information leads to developing hypothesis and approximation for the lunar operational needs, and lunar power demand analysis is driven by utilizing the data set. The above steps are defined to evolve a qualitative study for formulating different concepts and a thorough trade-off analysis addressed to select a concept. The above steps lead to the development of mathematical frameworks to fulfill the expected power demand. The study indicates that SBSP systems are a realistic and scalable alternative for satisfying the lunar economy’s energy demands, overcoming hurdles such as long lunar nights and harsh climatic conditions. Simulations and trade-off evaluations show that SBSP systems based on Microwave electricity Transmission (MPT) can offer continuous and dependable electricity. Economic budget estimates provide vital insights into the overall profitability and sustainability of the determined architectural concept. The findings show SBSP systems’ flexibility in dealing with lunar circumstances, integration possibilities with future infrastructure, and long-term cost advantages over alternative energy methods. While hurdles remain notably in lunar dust mitigation, SBSP promises a game-changing method to power long-term lunar operations, facilitating industrial growth and supporting human and robotic activities. Keywords: Space-Based Solar Power (SBSP); Microwave Power Transmission; Laser Power Transmission; Solar Reflectors; Lunar Surface Technology Research (LuSTR); Lunar Infrastructure; Lunar Exploration.
Keywords: Space-Based Solar Power (SBSP); Microwave Power Transmission; LaserPower Transmission; Solar Reflectors; Lunar Surface Technology Research (LuSTR); LunarInfrastructure; Lunar Exploration